Effects of Supplementing Sea Buckthorn Leaves (Hippophae rhamnoides L.) and Chromium (III) in Broiler Diet on the Nutritional Quality and Lipid Oxidative Stability of Meat - Mihaela Saracila; Arabela Elena Untea; Tatiana Dumitra Panaite; Iulia Varzaru; Alexandra-Gabriela Oancea; Raluca Paula Turcu; Petru Alexandru Vlaicu (MDPI AG, 2022)
Nowadays, the consumer trend towards healthier food choices is unquestionable. Meat products enriched with nutrients, such as polyunsaturated fatty acids and antioxidants, are gaining much more interest among consumers. However, products are susceptible to quality deterioration and a short shelf-life of meat through lipid oxidation due to the lack of antioxidants in the meat. In this regard, the efficacy of dietary sea buckthorn leaves (Hippophaë rhamnoides L.) together with Chromium on the nutritional quality of meat and lipid oxidative stability was investigated. An experiment (28 days long) was carried out on 90 Cobb 500 chickens assigned into three treatments: a control treatment based on corn and soybean meal, without Chromium (T0) and two treatments supplemented either with 0.00002% Chromium (T1) or with 0.00002% Chromium and 2% sea buckthorn leaves (T2). Dietary supplementation of SBL and Cr improved the PUFA/MUFA ratio, DHA concentration and decreased the n-6/n-3 ratio compared to the other treatments. Moreover, the breast and thigh meat belonging to T1 and T2 treatments showed a higher concentration of lutein and zeaxanthin, Fe and Zn and expressed a higher antioxidant capacity compared to those from T0. Furthermore, n-6 and n-3 PUFA deposited preferentially in the thigh meat rather than in the breast meat. The results from the study showed that dietary SBL and Cr significantly improved the fatty acid pattern and the oxidative stability of chicken breast meat, lowering the TBARS level after storage. In conclusion, SBL and Cr are promising dietary bioactive compounds with beneficial effects to obtain nutrient-enriched meat products.